A RAPID METHOD FOR DETERMINATION OF HYDROGEN AND OXYGEN ISOTOPE RATIOS FROM WATER AND HYDROUS MINERALS - Sharp Z.D.; Atudorei V.; Durakiewicz T. (My University, 2001)
A general-purpose, on-line, continuous flow method for determination of δD and δ18O values of water and hydrous minerals is described. Minor modifications of commercially available equipment allow for analyses of water and solid samples, fluid inclusions and in situ hydrogen isotope determinations of hydrous minerals using a laser. The technique involves reduction of H2O or solid hydrous samples by reaction with glassy carbon at high temperatures. H2 and CO are produced by reaction with the carbon at 1450°C in a helium carrier gas. Product gases are separated in a gas chromatograph and analyzed in a mass spectrometer configured to make hydrogen isotope analyses in continuous flow mode.Sample size is as small as 0.1 μl of water (or equivalent from hydrous phases) for both hydrogen and oxygen isotope ratio determinations. Waters are injected through a heated septa into the He stream; solid materials are wrapped in silver foil and dropped into the furnace using an autosampler. Using standard correction procedures, results obtained with this method are identical to those obtained conventionally with a precision for water samples of +/-2%% (1σ) for hydrogen and +/-0.2%% (1σ) for oxygen. Saline waters can be analyzed without any additional preparation. Reproducibility of δD values from hydrous silicates is also +/-2%% The δ18O values of 'dehydration' water evolved from biotite during heating is variable and irreproducible. Total time of analysis is less than 2 min for a single hydrogen isotope analysis.Sample size can be reduced an order of magnitude by using a low He-flow rate, a narrow-bore reduction column, a capillary GC column and a more efficient open split. With the high sensitivity design, in situ measurements can be made on hydrous minerals using a CO2 laser for sample heating. Stable isotope determinations of fluid inclusions can be made by decrepitating samples in the He-stream.
Keywords: STABLE ISOTOPES; GAS CHROMATOGRAPHY; METHODOLOGY; CARBON REDUCTION; IN SITU; FLUID INCLUSIONS